Cognitive Flexibility in terms of Mathematics Education Student Learning Outcomes - Hamdan Sugilar; Ida Nuraida; Ganiyu Habeeb (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Cognitive flexibility is the ability to think openly and be able to solve problems from different perspectives. People who have good cognitive flexibility will be able to learn faster, solve problems more creatively, and adapt and respond to new situations more effectively. This research method is a quantitative method of measuring the ability of cognitive flexibility as measured by questions that meet the indicators of cognitive flexibility with the object of research being the sixth semester student of one of the universities in the city of Bandung. The instrument consists of cognitive flexibility questions, theories about cognitive flexibility, and questionnaires. Processing of data by calculating the percentage of answering the questionnaire and scores of cognitive flexibility test scores in complex analysis courses. The results of the study showed that the ability to think openly, and many ideas and ideas about something was still low and the two abilities had a low correlation with lecture outcomes. So that the ability to think openly, and many ideas and ideas need to be improved so that students have an open mind and find new ideas in solving problems